Brunner's Gland Lesions in Rats Induced by a Vascular Endothelial Growth Factor Receptor Inhibitor. (December 2014) - Inomata, Akira; Nakano-Ito, Kyoko; Fujikawa, Yasuhiro; Sonoda, Jiro; Hayakawa, Kazuhiro; Ohta, Etsuko; Taketa, Yoshikazu; Van Gessel, Yvonne; Akare, Sandeep; Hutto, David; Hosokawa, Satoru; Tsukidate, Kazuo
Vascular endothelial growth factor (VEGF) receptor tyrosine kinase (RTK) inhibitors are reported to cause reversible mucosal hyperplasia (adenosis) in the duodenum of rats; however, the pathogenesis is not fully elucidated. Using lenvatinib, a VEGF RTK inhibitor, we characterized the histologic time course of this duodenal change in rats. At 4 weeks, there was degeneration and necrosis of Brunner's gland epithelium accompanied by neutrophil infiltration around the affected glands. At 13 weeks, the inflammation was more extensive, and Brunner's gland epithelium was attenuated and flattened and was accompanied by reactive hyperplasia of duodenal epithelium. At 26 weeks, the changes became more severe and chronic and characterized by marked cystic dilation, which extended to the external muscular layer. These dilated glands exhibited morphological characteristics of duodenal crypt epithelium, suggestive of replacement of disappeared Brunner's glands by regenerative duodenal crypt epithelial cells. Similar changes were not present in similar time course studies in dog and monkey studies, suggesting that this is a rodent- or species-specific change. Based on the temporal progression of Brunner's gland lesion, we identify degeneration and necrosis of the Brunner's glands as the primary change leading to inflammation, cystic dilatation, and regeneration with cells that are morphologically suggestive of duodenal crypt epithelium.